In Gratitude to Jim and Whit. Issue 157 (25th March 2018) - Greene, Jennifer C.
Abstract: Jennifer C. Greene relates stories about how she learned compassion for others and the importance of public education through watching her parents and participating in student protests during the 1960s. Then she learned about inquiry and discovered she could infuse these enduring commitments into evaluation practices conducted on behalf of others, especially those on society's margins. See the interview document here:http://onlinelibrary.wiley.com/wol1/doi/10.1002/ev.20291/suppinfo . Read only. This should not be used in any form without explicit permission from the author.